Immunomodulatory roles of selenium nanoparticles: Novel arts for potential immunotherapy strategy development - Chen, Gengshi; Yang, Fen; Fan, Shuhao; Jin, Hua; Liao, Kangsheng; Li, Xuemeng; Liu, Gan-Bin; Liang, Jing; Zhang, Junai; Xu, Jun-Fa; Pi, Jiang (Frontiers in Immunology, 2022)
Current chemotherapy strategies used in clinic appear with lots of disadvantages due to the low targeting effects of drugs and strong side effects, which significantly restricts the drug potency, causes multiple dysfunctions in the body, and even drives the emergence of diseases. Immunotherapy has been proved to boost the body’s innate and adaptive defenses for more effective disease control and treatment. As a trace element, selenium plays vital roles in human health by regulating the antioxidant defense, enzyme activity, and immune response through various specific pathways. Profiting from novel nanotechnology, selenium nanoparticles have been widely developed to reveal great potential in anticancer, antibacterial, and anti-inflammation treatments. More interestingly, increasing evidence has also shown that functional selenium nanoparticles can be applied for potential immunotherapy, which would achieve more effective treatment efficiency as adjunctive therapy strategies for the current chemotherapy. By directly interacting with innate immune cells, such as macrophages, dendritic cells, and natural killer cells, selenium nanoparticles can regulate innate immunity to intervene disease developments, which were reported to boost the anticancer, anti-infection, and anti-inflammation treatments. Moreover, selenium nanoparticles can also activate and recover different T cells for adaptive immunity regulations to enhance their cytotoxic to combat cancer cells, indicating the potential of selenium nanoparticles for potential immunotherapy strategy development. Here, aiming to enhance our understanding of the potential immunotherapy strategy development based on Se NPs, this review will summarize the immunological regulation effects of selenium nanoparticles and the application of selenium nanoparticle-based immunotherapy strategies. Furthermore, we will discuss the advancing perspective of selenium nanoparticle-based potential immunotherapy as a kind of novel adjunctive therapy to enhance the efficiency of current chemotherapies and also introduce the current obstacles for the development of selenium nanoparticles for potential immunotherapy strategy development. This work is expected to promote the future research on selenium nanoparticle-assisted immunotherapy and finally benefit the more effective disease treatments against the threatening cancer and infectious and chronic diseases.